2004
DOI: 10.1002/ijc.11606
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the level of mRNA expression of the membrane regulators of complement, CD59, CD55 and CD46, in breast cancer

Abstract: We have examined the relative mRNA expression of the complement (C) regulatory proteins CD59, CD55 and CD46 in RNA isolated from 50 primary breast cancer specimens using a semiquantitative RT-PCR approach. Having normalized the mRNA expression levels of the C regulators relative to actin, we subsequently correlated their expression with estrogen receptor (ER) and various clinical, pathologic and biochemical features of the disease. CD59 and CD46 were detected in all clinical biopsies, while CD55 mRNA was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…After infection, the cells were collected at the indicated time points and total RNA was isolated from the cells using Isogen reagent (Nippon Gene, Tokyo, Japan). First-strand cDNA templates were synthesized as previously described, 43 and the templates were subjected to PCR amplification using sets of primers for human CD46 45 and GAPDH. 46 The cycling parameters were 30 s at 941C, 30 s at 551C and 30 s at 721C for both CD46 and GAPDH.…”
Section: Rt-pcr Analysis For Cd46 Expressionmentioning
confidence: 99%
“…After infection, the cells were collected at the indicated time points and total RNA was isolated from the cells using Isogen reagent (Nippon Gene, Tokyo, Japan). First-strand cDNA templates were synthesized as previously described, 43 and the templates were subjected to PCR amplification using sets of primers for human CD46 45 and GAPDH. 46 The cycling parameters were 30 s at 941C, 30 s at 551C and 30 s at 721C for both CD46 and GAPDH.…”
Section: Rt-pcr Analysis For Cd46 Expressionmentioning
confidence: 99%
“…CReg are broadly expressed on a wide variety of tissues and cells, including epithelial, endothelial, and circulatory cells, and act as physiologic brakes to complement amplification. CD46, CD55, and CD59 are expressed on a number of solid tumors and associated cell lines, and it is apparent that the level of expression in malignant tissue is often greater than that seen in the normal surrounding tissue (7,(11)(12)(13). Consequently, the increased complement resistance conferred by these membrane-bound CReg has been proposed as a mechanism that facilitates survival of the tumor or the metastasizing tumor cell when it enters circulation (8,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The high expression of this receptor may offer a growth advantage to cancer cells by protecting them from complement damage. [35][36][37][38] This increased expression on many different cancer types including pancreatic cancer renders CD46 an ideal target to obtain specific transduction of tumors. Here we showed that exchanging the fiber of Ad5 with fibers of serotype 16 and 50 indeed resulted in an enhanced gene transfer to human pancreatic adenocarcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%